Sosialisasi Potensi Risiko MSDs Pada Postur Tubuh Pekerja Di PT SKF Indonesia - Amanulloh, Muhammad Daffa; Pradana, Aditya Wahyu (Journal of Community Services in Sustainability, 2024)
PT SKF Indonesia is a company engaged in the production of automotive parts in the form of bearings. In the initial observations, the problem was identified as poor working posture of the operators resulting in musculoskeletal disorderrisk (MSDs). The observed risks are in several areas of the body such as arms, shoulders, calves, and others. The analysis carried out consisted of carrying out RULA and REBA methods to identify potential risks of MSDs in certain parts of the operator’s body. This service activity is expected to bring benefits to the company in the form of solutions that will improve the company’s performance and reduce the expected accidents to zero, as it aims to identify all potential risks in all areas of work.